Exploring German High School Students' Conceptual Learning Pathways of Space and Place - Natalie Bienert (MDPI AG, 2024)
Space and place, fundamental concepts in geography, uniquely contribute to the development of students' geographical thinking. Despite this, these concepts are underrepresented in German geography classrooms, partly due to a distinct lack of empirical evidence concerning the learning processes associated with learning complex geographical concepts. This study employed videography to explore how n = 64 grade twelve students from various school types in Germany develop a more sophisticated understanding of space and place during a 90 min. teaching experiment. To delve into the micro-level of students' learning processes, qualitative content analysis was employed to analyse the data. The subsequent detailed reconstruction of an individual learning pathway unveiled several pivotal moments. Notably, the concepts demonstrated significant potential for restructuring students' existing knowledge into a more conceptual and systematic framework. Moreover, barriers to learning were identified as well. For example, conceptual interferences between the concepts of space/place and other geographical key concepts such as sustainability were observed, partially impeding the formation of a clear conceptual framework in students' minds. The results provide insights for teaching implications, such as emphasising a single key concept to avoid conceptual interferences, and suggest further research avenues, including longitudinal studies to empirically derive learning progressions related to space and place.